Increased neutrophil-to-lymphocyte ratio predicts persistent coronary no-flow after wire insertion in patients with ST-elevation myocardial infarction undergoing primary percutaneous coronary intervention (Clinics, 2015)
OBJECTIVES: Acute ST-segment elevation myocardial infarction patients presenting persistent no-flow after wire insertion have a lower survival rate despite successful mechanical intervention. The neutrophil-to-lymphocyte ratio has been associated with increased mortality and worse clinical outcomes in ST-segment elevation myocardial infarction. We hypothesized that an elevated neutrophil-to-lymphocyte ratio would also be associated with a persistent Thrombolysis In Myocardial Infarction flow grade of 0 after wire insertion in patients undergoing primary percutaneous coronary intervention. METHODS: A total of 644 patients with ST-segment elevation myocardial infarction who underwent primary percutaneous coronary intervention within 12 hours of symptom onset were included in our study. Blood samples were drawn immediately upon hospital admission. The patients were divided into 3 groups according to their Thrombolysis In Myocardial Infarction flow grade: Thrombolysis In Myocardial Infarction flow grade 0 after wire insertion, Thrombolysis In Myocardial Infarction flow grade 1-3 after wire insertion and Thrombolysis In Myocardial Infarction flow grade 1-3 at baseline. RESULTS: The neutrophil-to-lymphocyte ratio was significantly higher in the group with Thrombolysis In Myocardial Infarction flow grade 0 after wire insertion compared with the group with Thrombolysis In Myocardial Infarction flow grade 1-3 after wire insertion and the group with Thrombolysis In Myocardial Infarction flow grade 1-3 at baseline. The group with Thrombolysis In Myocardial Infarction flow grade 0 after wire insertion also had a significantly higher in-hospital mortality rate. Persistent coronary no-flow after wire insertion was independently associated with the neutrophil-to-lymphocyte ratio. CONCLUSIONS: An increased neutrophil-to-lymphocyte ratio on admission is significantly associated with persistent coronary no-flow after wire insertion in patients with ST-segment elevation myocardial infarction undergoing primary percutaneous coronary intervention.